Renewable energy and energy security : Alternative pathway to fossil energy imports consumption in Finland - Loven, Vesa (My University, 2022)
Renewable energy sources (RES) have an essential role in substituting traditional fossil fuels, oil, natural gas, and coal. Besides being considered a desirable target from the environmental conservation point of view, renewable energy deployment can additionally offer an effective tool for improving energy security. Many countries, including Finland, import fossil energy from concentrated energy sources. Therefore, the deployment of renewable energy can diversify the energy supply and reduce the dependence on fossil energy imports. Even though the subject is widely acknowledged, empirical analysis of the effects is not so far broadly available, especially in the case of Finland. This master’s thesis discusses the role of RES in the energy security of Finland from the perspective of import dependence. The study empirically assesses the effects of renewable energy consumption on fossil energy imports consumption in the country between 2000–2020. The literature review covers an overview of energy supply and demand in Finland, as well as a recent development and future views of domestic renewable energy sources. Furthermore, the concept of energy security and the complexity of determining the issue, along with the energy security views of the country, are addressed. The literature review concludes with the theoretical framework on the relationship between renewable energy deployment and energy security. The empirical analysis utilizes time series regarding energy consumption in the country in 20 years period, sourced from the Official Statistics of Finland database. Multiple linear regression analysis is then applied to assess the effects of renewable energy sources' consumption on fossil energy imports consumption in the period. A series of regression diagnostic tests along with stability testing supports the correctness of the empirical models employed for the investigation. Key findings first discover that RES consumption shows a declining effect on coal and oil consumption, but the development of natural gas import consumption is not explained by RES with the model used. The conclusion is drawn that renewable energy has been successfully utilized to decrease coal and oil imports consumption rather than natural gas imports. Further, findings underline, besides hydropower, decreasing effect of marginal RES alternatives combined (wind energy, solar power, liquid biofuels, and heat pumps) on coal and oil consumption in the country between 2000–2020. In addition, the role of direct electricity imports in compensating for fossil energy consumption reflects in the results. The findings of the study are largely parallel to previous literature in Europe and contribute to the evidence of RES enabling improvements in energy security.

Uusiutuvalla energialla on keskeinen rooli perinteisten fossiilisten polttoaineiden, öljyn, maakaasun ja hiilen korvaamisessa. Sen lisäksi, että uusiutuvan energian käyttöä pidetään ympäristön kannalta vähemmän haitallisena vaihtoehtona, se voi olla keino energiaturvallisuuden parantamiseen. Monet Euroopan maat kuten Suomi, tuovat fossiilisia polttoaineita keskittyneistä energialähteistä. Uusiutuvan energian käyttöönotto voi hajauttaa energian tarjontaa ja vähentää riippuvuutta fossiilisesta tuontienergiasta. Asia on laajasti tunnistettu tutkimuskirjallisuudessa mutta empiiristä analyysia vaikutuksista etenkään Suomessa ei vielä ole kattavasti saatavilla. Tämä taloustieteen pro gradu -tutkielma käsittelee uusiutuvan energian roolia Suomen energiaturvallisuudessa, fossiilisen tuontienergian ja tuontiriippuvuuden näkökulmasta. Tutkielman tavoitteena on empiirisesti analysoida uusiutuvan energian kulutuksen vaikutuksia fossiilisten polttoaineiden kulutukseen Suomessa vuosina 2000–2020. Kirjallisuuskatsaus esittelee energian tarjonnan ja kysynnän keskeiset piirteet sekä uusiutuvan energian käytön maassa. Lisäksi käsitellään energiaturvallisuuden määrittelyä sekä Suomen energiaturvallisuuden näkymiä. Näin muodostuu teoreettinen viitekehys uusiutuvan energian mahdollisista vaikutuksista energiaturvallisuuteen. Tutkielman empiirisessä analyysissä hyödynnetään Tilastokeskuksen tietokannasta kerättyjä aikasarja-aineistoja energiankulutuksesta 20 vuoden ajanjaksolta Suomessa. Lineaarista regressioanalyysia soveltamalla arvioidaan eri uusiutuvien energialähteiden vaikutuksia fossiilisten polttoaineiden tuonnin kulutukseen vuosina 2000–2020. Regressioanalyysin tulokset varmistetaan sarjalla diagnostisia testejä. Empiiriset havainnot osoittavat uusiutuvan energian vähentävän vaikutuksen hiilen ja öljyn tuonnin kulutuksessa. Maakaasun tuonnin kulutuksen kehitystä ei kuitenkaan voida selittää käytetyssä mallissa uusiutuvan energian kulutuksella. Tulos viittaa siihen, että uusiutuvaa energiaa on onnistuneesti hyödynnetty vähentämään hiilen ja öljyn tuonnin kulutusta maakaasun kulutuksen sijaan. Muiden keskeisten havaintojen mukaan hiilen ja öljyn kulutukseen vuosina 2000–2020 on vaikuttanut vähentävästi vesivoiman lisäksi muut osuuksiltaan pienemmät uusiutuvat energialähteet yhdessä: tuulivoima, aurinkovoima, nestemäiset biopolttoaineet ja lämpöpumput. Uusiutuvan energian lisäksi tuontisähkön merkitys fossiilisen tuontienergian korvaamisessa näkyy tuloksissa. Löydökset ovat pitkälti samankaltaisia aiempien eurooppalaisten tutkimustulosten kanssa ja antavat osaltaan näyttöä uusiutuvan energian mahdollisista energiaturvallisuutta parantavista vaikutuksista.
Keywords: fossil fuels; renewable energy sources; security of energy supply; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|; Taloustiede